PERSEPSI GURU TERHADAP PELAKSANAAN KEGIATAN KELOMPOK KERJA GURU (KKG) DI SDN KECAMATAN KAYU ARO KABUPATEN KERINCI - Yani Fk; Hadiyanto Hadiyanto; Hanif Alkadri (Journal of Educational Administration and Leadership, 2020)
The purpose of this research is to look for information about the teacher perception of the Implementation of Teacher Work Group (TWG) on primary schools in Kayu Aro district. This is a descriptive research. The population is 85 teachers and sample is 66 teachers that are taken by simple random sampling. The instrument of this research was a questionnaire with Likert scale models that had been tested for validity and reliability. The data were analyzed using the average (mean) formula. The results of this research show that the teacher perception about the Implementation of Teacher Work Group (TWG) in primary schools in Kayu Aro district stay in good category with an average score of 3.90